2022
DOI: 10.1101/gr.276059.121
|View full text |Cite
|
Sign up to set email alerts
|

Identification of phenotype-specific networks from paired gene expression–cell shape imaging data

Abstract: The morphology of breast cancer cells is often used as an indicator of tumor severity and prognosis. Additionally, morphology can be used to identify more fine-grained, molecular developments within a cancer cell, such as transcriptomic changes and signalling pathway activity. Delineating the interface between morphology and signalling is important to understand the mechanical cues that a cell processes in order to undergo epithelial-to-mesenchymal transition and consequently metastasize. However, the exact re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 120 publications
0
6
0
Order By: Relevance
“…To investigate the origins of the intergastruloid heterogeneity, we used Weighted Gene Co-Expression Network Analysis (WGCNA) to find biological properties significantly associated with our phenotype of interesty (Barker et al, 2022;Langfelder and Horvath, 2008). For this we first ran single cell WGCNA (Feregrino and Tschopp, 2021) on only the day 3 MULTI-seq cells.…”
Section: Varying Wnt Responses At Day 3 Explain Gastruloid Bifurcationmentioning
confidence: 99%
“…To investigate the origins of the intergastruloid heterogeneity, we used Weighted Gene Co-Expression Network Analysis (WGCNA) to find biological properties significantly associated with our phenotype of interesty (Barker et al, 2022;Langfelder and Horvath, 2008). For this we first ran single cell WGCNA (Feregrino and Tschopp, 2021) on only the day 3 MULTI-seq cells.…”
Section: Varying Wnt Responses At Day 3 Explain Gastruloid Bifurcationmentioning
confidence: 99%
“…Taken together, GBM cell morphology mediates intercellular communication and thus has important consequences on tumor cell proliferation, survival, invasiveness and resistance to therapy. Hence, in GBM, like in other cancers (Alizadeh et al, 2020; Barker et al, 2022; Wu et al, 2020), cell morphology has a strong potential to be used as a diagnostic and prognostic marker, through microscopy-based analysis of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…The morphological changes in breast cancer models are often used to indicate the high transformational characteristics of those cells ( Barker et al, 2022 ). We found that proteins associated with aggressive basal-like phenotype were found to be increased in our phosphoproteomic screen, which included ADGRA2 (S1079) and DENND4C (S1250).…”
Section: Discussionmentioning
confidence: 99%